Comparing the Effect of Using DC Fans and Heatsinks As Cooling Systems on Photovoltaic Efficiency - Hakim, Muhammad Fuad Abdul; Putra, Mohammad Alexin; Nurhilal, Otong (TURBO [Tulisan Riset Berbasis Online], 2023)
One of the utilizations of solar energy is to be converted into electricity using photovoltaics (PV). The most important performance parameter of PV is efficiency. The efficiency will decrease as the PV temperature increases. Therefore, a cooling system is needed to increase PV efficiency. The objective of the research is to determine and compare the effect of DC fan and heatsink as a cooling system on PV efficiency. Four PV units with a capacity of 30 WP are used. The experiment is conducted as follows, the first PV is equipped with DC fan cooling, the second PV with heatsink cooling, the third PV with a combination of DC fan and heatsink cooling, and the fourth PV is without cooling as a reference. The result shows, that the combination of DC fan and heatsink cooling system provides the highest efficiency improvement, namely 32.08%, followed by DC fan cooling, namely 16.04%. As for heatsink cooling, there is no improvement in efficiency. The combination of DC fan and heatsink cooling system can dissipate heat from the PV more effectively than DC fan cooling system, so the PV temperature is lower and produces higher output power and efficiency. The heatsink cooling system is not effective in dissipating heat because of limited natural airflow due to the low PV stand which is only 30 cm from the ground.